A JOURNEY ACROSS SELECTED OUTCROPS IN ALPINE CORSICA: A SHOWCASE OF THE OCEANIC AND CONTINENTAL UNITS OF A COLLISIONAL BELT - Marroni, Michele; Pandolfi, Luca; Di Rosa, Maria; Frassi, Chiara; Malasoma, Alessandro; Meneghini, Francesca (Ofioliti, 2026)
This paper describes a four-day field trip across the Alpine Corsica, the southern branch of the Alpine collisional belt made up of oceanic and continental units derived from the closure of the Ligurian-Piedmont Oceanic Basin, and the subsequent collision between the continental margins of Adria and Europe plates. On the first day, the relationships between the main tectonic units, i.e., the Upper Units, the Schistes Lustrés Complex and the Lower Units, can be observed along an east-west transect from Bastia to Ile-Rousse. On the second day, the features of the Upper Units can be observed in the Balagne area, where an ophiolite sequence from the Middle to Late Jurassic period, along with its Late Jurassic to Late Cretaceous sedimentary cover, is clearly visible. This sequence, belonging to the Balagne Nappe, is characterized by the repeated occurrence of coarse-grained deposits supplied from the Europe continental margin, which makes it unique in the Alpine-Apennine belt. On the third day, the oceanic units of the Schistes Lustrés Complex in the Golo Valley will be examined. This complex comprises several ophiolite sequences that were accreted to the Alpine wedge and deformed under conditions of pressure and temperature ranging from blueschist to eclogite facies. On the fourth day, the Lower Units in the Corte, Popolasca and Ponte Leccia areas are visited. These units represent slices of the thinned continental margin of the Europe plate that were involved in subduction prior to continental collision. Overall, this paper provides a comprehensive overview of the stratigraphic, deformational, and metamorphic features of Corsica, which is one of the most significant fragments of the Alpine collisional belt in the western Mediterranean region.